Cyiology of some Varieties of Ziziphus jujuba Lamk - Sareen, T. S.; Singh, P. D. (Indian Forester, 1976)
Eight varieties of Ziziphus jujuba have heen cytologically investigated. Of these seven varieties are tetraploids (n = 24), being reported here for the first time, while one is hexaploid with n=36. Jogia exhibits normal meiotic behaviour. The formation of variable number of quadrivalents in others seem to indicate their segmental alloploid origin.